Uncovering mechanisms behind microbiota-induced neuroprotection in C. elegans models of Alzheimer’s disease - Pho, Kim (My University, 2023)
Alzheimer’s Disease (AD) is the most common neurodegenerative disorder worldwide. The risk of developing AD is influenced not only by genetic factors, but also the environment. The multi-factored pathogenesis that leads to AD development poses a challenge for identifying causal factors that promote or protect against neurodegeneration. We use Caenorhabditis elegans as a model of AD to measure the impact of human microbiota species on AD-related phenotypes. The two hallmarks of AD are amyloid-β (Aβ) plaques and neurofibrillary tangles composed of the protein tau. Using a C. elegans model overexpressing Aβ, we identified a group of Enterobacteriaceae species that significantly reduce paralysis. To validate these findings, we used another C. elegans model that pan-neuronally expressed aggregate-prone tau (AP-tau). We observed decreased neurodegeneration in response to most of the same bacteria protective against Aβ-induced paralysis, providing additional evidence of microbiota-promoted neuroprotection. To explore the underlying host mechanisms, we examined gene expression changes in animals exposed to neuroprotective bacteria. Numerous biological processes were differentially regulated in response to the neuroprotective microbiota species, including innate immunity, stress responses, and protein phosphorylation. Several C. elegans orthologs of human tau tubulin kinase genes, TTBK1 and TTBK2, were downregulated in response to neuroprotective microbiota species. RNAi-mediated knockdown of C. elegans ttbks sufficiently induced neuroprotection in AP-tau animals. Further, Enterobacter caused decreased abundance of a tau species phosphorylated at S422, a TTBK1 direct phosphorylation site. These findings suggest that species from the human microbiota can reduce tau phosphorylation, and mediate neuroprotection through downregulation of ttbk. Overall, by studying the impact of the human microbiota on models overexpressing Aβ or AP-tau, we have uncovered a potential mechanism by which microbiota-mediated neuroprotection can occur. In doing so, we also gain a greater understanding of conserved pathways involved in gene-environment interactions promoting development of AD.